2022
DOI: 10.3390/plants11040475
|View full text |Cite
|
Sign up to set email alerts
|

Metals Induce Genotoxicity in Three Cardoon Cultivars: Relation to Metal Uptake and Distribution in Extra- and Intracellular Fractions

Abstract: Heavy metal-polluted soil represents an important stress condition for plants. Several studies demonstrated that growth inhibition under metal stress and metal-induced damages, including genotoxicity, is particularly pronounced at the early stages of seedling growth. Moreover, it is reported that heavy metals enter the cytoplasm to exert their detrimental effect, including DNA damage. In this work, we estimated (i) metal-induced genotoxicity by ISSR molecular markers and (ii) the distribution of the metal frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Three young leaves (15 d), at the same development stage, were selected from three plants for each treatment (control, 1 and 10 Gy X-ray irradiation), and DNA-extracted and amplified following Sorrentino et al (2022) . In brief, total genomic DNA was extracted by using a modified CTAB (cetyl-trimethyl ammonium bromide) method ( Murray & Thompson, 1980 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three young leaves (15 d), at the same development stage, were selected from three plants for each treatment (control, 1 and 10 Gy X-ray irradiation), and DNA-extracted and amplified following Sorrentino et al (2022) . In brief, total genomic DNA was extracted by using a modified CTAB (cetyl-trimethyl ammonium bromide) method ( Murray & Thompson, 1980 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the comet assay revealed dose‐dependent DNA damage and chromatin pulverization in the root tips of Allium cepa and Vicia faba exposed to Ni (Cortés‐Eslava et al, 2018). Using Inter Simple Sequence Repeats (ISSR) markers, Sorrentino et al (2022) showed that Cd and Pb caused DNA damage in three cardoon ( Cynara cardunculus ) cultivars. Genotoxicity may arise from both direct reactions of trace metals with DNA or proteins associated with the DNA repair system, and oxidative stress generated by trace metal toxicity.…”
Section: Toxicity Of Trace Metals To Plantsmentioning
confidence: 99%